FAMILY ROLE IN OPTIMIZING ‘STUDY FROM HOME’ WITH MERDEKA BELAJAR APPROACH - Sakti, M. Nawa Syarif Fajar; Darsim, Sitti Fathimah Herdarina (Proceeding of International Conference on Islamic Education (ICIED), 2021)
The Covid-19 pandemic changed all aspects of life and the government tried to reduce transmission more quickly through policies to maintain social distance. One of them is in education the learning process at school is shifted to learning at home, the policy reaps controversy between parents and teachers who experience difficulties in the learning process. Some newspapers mention complaints about e-learning facilities that are less supportive which has an impact on children's learning difficulties. But, the family aspect in education is not widely mentioned, even though family education is very important. This article seeks to explain the role of the family in children's education which begins to fade when the family occupies an important role in the learning process in the midst of the co-19 pandemic using library research methods. Through the Merdeka Belajar approach that carries literacy, numeracy and personality, the role of the family through its functions in education can be optimized in improving children's learning at home.